2017
DOI: 10.29252/jhehp.2.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Behavior of Female Students of School of Paramedical and Health in Zanjan

Abstract: Proper and useful nutrition is one of the important, essential and vital factors in providing individuals, family and society health and safety. Suitable food provides movement and activity, satisfaction, vitality and ability to fight with the health problems as well as the health of the next generations [1, 2]. There are different food patterns between people at different levels of socioeconomic status, races, societies and cultures, and the socioeconomic development of any society is directly related to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…On Hungarian university students showed that students' diets rarely consumed vegetables and fruit [7]. In other studies, it appears that healthy students still have bad eating habits such as consuming junk food and soft drinks [8]. From this study, lousy food consumption patterns in students can lead to poor nutritional status.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…On Hungarian university students showed that students' diets rarely consumed vegetables and fruit [7]. In other studies, it appears that healthy students still have bad eating habits such as consuming junk food and soft drinks [8]. From this study, lousy food consumption patterns in students can lead to poor nutritional status.…”
Section: Introductionmentioning
confidence: 62%
“…Foods with high energy density contain a large amount of energy per gram of food weight. Consumption of foods with high energy density will increase energy intake and body fat to increase the risk of obesity [8]. According to the Indonesian Nutritional Adequacy Rate, the results showed that only three students had excessive food intake, but 15 people were overweight, and 27 were obese.…”
Section: Discussionmentioning
confidence: 99%